Identification of reducing and nonreducing neutral carbohydrates by laser‐enhanced in‐source decay (LEISD) MALDI MS. (19th April 2013) - Yang, Hongmei; Li, Zong‐Jun; Wan, Debin; Lian, Wenhui; Liu, Shuying
<x xml:space="preserve">Abstract</x> In this work, laser‐enhanced in‐source decay (LEISD) technique of matrix‐assisted laser desorption/ionization Fourier transform ion cyclotron resonance mass spectrometry (MALDI‐FT‐ICR‐MS) was used to distinguish reducing and nonreducing carbohydrates. Interestingly, easier cleavage of (1 → 2)‐linked glycosidic bonds for nonreducing carbohydrates containing D‐fructofuranosyl units was observed in MALDI‐FT‐ICR‐MS, which was in agreement with the result of theoretical calculation by the software package Gaussian 09. Importantly, no cross‐ring cleavage of fructofuranosyl residues was detected in the LEISD spectra of nonreducing carbohydrates. LEISD method therefore offers an attractive alternative for fast and efficient differentiation of reducing and nonreducing carbohydrates, and the positions of nonreducing monosaccharide residues in a carbohydrate chain could be easily speculated. Copyright © 2013 John Wiley & Sons, Ltd.